Does Managerial Ownership Moderate the Relationship between Corporate Social Responsibility Disclosure and Tax Aggressiveness? (Evidence from Mining Companies in Indonesia) - Anggraeni, Devi Putri; Hastuti, Sri (JASF: Journal of Accounting and Strategic Finance, 2020)
Companies' disclosure is an important thing to do because it is one of the corporate governance concepts. The purpose of this study is first to investigate the influence of corporate social responsibility disclosure on corporate tax aggressiveness. Also, to prove the influence of managerial ownership as a moderating variable in the relationship between corporate social responsibility and tax aggressiveness. This study uses secondary data, namely financial statements and annual reports that have been published by companies on the Indonesia Stock Exchange and the company's website. This study's population are mining companies listed on the Indonesia Stock Exchange during the 2014-2018 period. Using the purposive sampling method, the total sample of this study is 30 data from 39 companies. Data were analyzed by descriptive analysis and multiple regression analysis. The results of this study indicate that Corporate social responsibility disclosure affects tax aggressiveness. And managerial ownership as a moderating variable affects the relationship between corporate social responsibility disclosure and tax aggressiveness. It is suggested that companies must pay attention to the CSR disclosure and ownership structure and their relationship with tax aggressiveness.